High-flux nanofiltration membrane with gradient pore structure as well as preparation method and application of high-flux nanofiltration membrane
By designing a gradient pore structure in the nanofiltration membrane and combining interfacial polymerization technology, the contradiction between water flux and selectivity of the existing nanofiltration membrane is solved, and a high-throughput and high-selectivity nanofiltration membrane is achieved.
Patent Information
- Application Number
- CN202510165436.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-04-25
AI Technical Summary
The existing nanofiltration membranes have low water flux while ensuring high selectivity, which affects the treatment efficiency.
By designing a new reaction monomer and regulating the interfacial polymerization process, a nanofiltration membrane with a gradient pore structure was prepared. The specific steps include performing primary and secondary interfacial polymerization reactions on the surface of the porous support membrane to form a relatively dense polyamide surface layer and a relatively loose polyester base layer.
It significantly improves the water flux and selectivity of the nanofiltration membrane, solving the "trade-off" effect between the water flux and selectivity of the traditional nanofiltration membrane.
Smart Images

Figure CN119869249A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of membrane separation, and in particular to a high-flux nanofiltration membrane with a gradient pore structure and a preparation method and application thereof. Background Art
[0002] With the rapid growth of population and the rapid development of society, a large number of pollutants with biological toxicity, environmental persistence and bioaccumulation have entered the water environment, posing a huge challenge to global drinking water safety. Nanofiltration is a new water treatment technology that can effectively intercept organic matter with a molecular weight between 200-1000Da. It has the characteristics of high filtration accuracy and low energy consumption, and has shown a strong competitive advantage in the deep purification of drinking water.
[0003] Existing commercial nanofiltration membranes are mainly aromatic polyamide composite membranes, which are mainly composed of three parts: a polyamide separation layer, a porous support layer (generally an ultrafiltration membrane) and a non-woven fabric layer. In the membrane separation process, the microporous structure of the separation layer is a key factor affecting the mass transfer of the composite membrane and determines the permeability of the nanofiltration membrane. However, limited by the "trade-off" effect between the water flux and selectivity of the nanofiltration membrane, the polyamide separation layer with a dense structure formed by the interfacial polymerization of highly reactive water phase and oil phase monomers, while ensuring high selectivity, usually has a relatively low water flux, which seriously affects the treatment efficiency of the nanofiltration membrane.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a high-flux nanofiltration membrane with a gradient pore structure and a preparation method and application thereof. The high-flux nanofiltration membrane has excellent water flux and selectivity.
[0006] The present invention provides a method for preparing a high-flux nanofiltration membrane with a gradient pore structure, comprising the following steps performed in sequence:
[0007] S1: pouring the first aqueous phase solution onto the surface of the fixed porous support membrane, and after soaking for a certain period of time, pouring out the first aqueous phase solution and removing the residual solution on the surface of the porous support membrane;
[0008] S2: pouring the oil phase solution onto the surface of the porous support membrane to carry out an interfacial polymerization reaction, then pouring out the oil phase solution and blowing the surface of the porous support membrane until there is no residual solvent, thereby obtaining a primary membrane;
[0009] S3: pouring the second aqueous phase solution onto the surface of the primary membrane to carry out a secondary interfacial polymerization reaction, and then pouring out the second aqueous phase solution to obtain a composite membrane;
[0010] S4: heat-treating the composite membrane to obtain a high-flux nanofiltration membrane with a gradient pore structure.
[0011] In step S1, the porous support membrane is selected from any one of cellulose acetate ultrafiltration membrane, polyethylene ultrafiltration membrane, polysulfone ultrafiltration membrane, polyethersulfone ultrafiltration membrane, polyamide ultrafiltration membrane, and polyacrylonitrile ultrafiltration membrane.
[0012] The solute of the first aqueous phase solution includes aqueous phase monomers and acid binding agents; the solvent of the first aqueous phase solution can be ultrapure water or the like.
[0013] The aqueous phase monomer is selected from at least one of self-microporous polymers containing at least two hydroxyl groups, and can be selected from at least one of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane, 3,3,3',3'-tetramethyl-1,1'-spiro BI (indane)-6,6'-diol, 9,9-bis (4-hydroxy-3-methylphenyl) fluorene and bisphenol fluorene. The mass concentration of the aqueous phase monomer in the first aqueous phase solution is 1-10wt%, for example, 1-2wt%.
[0014] The acid binding agent is selected from at least one of triethylamine, sodium hydroxide, potassium hydroxide, pyridine, N,N-diisopropylethylamine, trisodium phosphate dodecahydrate and sodium carbonate, and the mass concentration of the acid binding agent in the first aqueous phase solution is 0.1-5wt%, for example, 0.5-2wt%.
[0015] The first aqueous phase solution is infiltrated on the surface of the porous support membrane for 1-10 minutes, for example, 2-5 minutes.
[0016] In step S2, the solute of the oil phase solution includes an oil phase monomer; and the solvent of the oil phase solution is selected from at least one of n-hexane, Isopar G and toluene.
[0017] The oil phase monomer is selected from at least one of polyacid chlorides, and can be selected from at least one of trimesoyl chloride, terephthaloyl chloride and isophthaloyl chloride; the mass concentration of the oil phase monomer in the oil phase solution is 0.1-5wt%, for example 0.1-0.5wt%.
[0018] The time of one interfacial polymerization reaction is 1-10 min, for example, 2-5 min.
[0019] In step S3, the solute of the second aqueous phase solution contains only aqueous phase monomers; the solvent of the second aqueous phase solution can be ultrapure water or the like.
[0020] The aqueous phase monomer is selected from at least one of amine compounds, and can be selected from at least one of m-phenylenediamine, piperazine, ethylenediamine and diethylenetriamine; the mass concentration of the aqueous phase monomer in the second aqueous phase solution is 1-10wt%, for example, 1-1.5wt%.
[0021] The secondary interfacial polymerization reaction time is 1-10 min, for example, 2-5 min.
[0022] In step S4, the heat treatment temperature is 50-100° C., for example, 65-95° C.; the heat treatment time is 1-15 min, for example, 3-8 min.
[0023] The preparation method of the present invention adjusts the microporous structure of the nanofiltration membrane separation layer by designing a new type of reaction monomer and regulating the interfacial polymerization reaction process; specifically as follows: first, on the surface of the porous support membrane, a self-microporous polymer with a rigid twisted structure and a polyacyl chloride are subjected to a primary interfacial polymerization to prepare a relatively loose polyester bottom layer containing an inherent microporous structure, not easy to compact, and having high mechanical strength, and then a secondary interfacial polymerization is performed using the residual acyl chloride groups and amine compounds on the surface of the polyester bottom layer after the primary interfacial polymerization reaction to prepare a relatively dense and thin polyamide surface layer, thereby preparing a nanofiltration membrane with a gradient pore structure having a dense surface layer and a loose main body. Since the prepared nanofiltration membrane separation layer has a thin surface thickness and the polyester main body containing an inherent microporous structure is relatively loose, a channel is provided for water penetration, which significantly improves the water flux of the nanofiltration membrane; at the same time, the relatively dense surface of the separation layer ensures the high selectivity of the nanofiltration membrane, so that the nanofiltration membrane has excellent water flux and selectivity at the same time.
[0024] The present invention also provides a high-flux nanofiltration membrane with a gradient pore structure, which is prepared according to the above preparation method.
[0025] The high flux nanofiltration membrane of the invention is composed of a relatively dense polyamide surface layer with high selectivity and a relatively loose polyester bottom layer with extremely high water flux.
[0026] The present invention also provides application of the high-flux nanofiltration membrane in water treatment.
[0027] The implementation of the present invention has at least the following advantages:
[0028] 1. The preparation process of the present invention is simple, has strong controllability, low equipment requirements, and is convenient for large-scale production.
[0029] 2. The present invention designs the nanofiltration membrane separation layer layer by layer. First, a relatively loose polyester separation layer bottom layer with an inherent microporous structure, not easy to compact, and high mechanical strength is constructed on the surface of the porous support membrane. Then, a relatively dense and thin polyamide separation layer surface layer is constructed on this basis, thereby preparing a high-flux nanofiltration membrane with a gradient pore structure; wherein, the thin thickness and high density of the separation layer surface layer ensures the high selectivity of the nanofiltration composite membrane while having a small transmembrane resistance, and the relatively loose separation layer bottom layer with an inherent microporous structure provides a channel for water penetration, which significantly improves the water flux of the nanofiltration membrane; in addition, the rigid twisted structure of the microporous polymer in the separation layer bottom layer provides the nanofiltration composite membrane with sufficiently high mechanical strength.
[0030] 3. The high-flux nanofiltration membrane separation layer with a gradient pore structure provided by the present invention is composed of a relatively dense surface layer and a relatively loose bottom layer. The water flux and selectivity are superior to the single-layer polyamide separation layer nanofiltration membrane prepared by the current traditional interfacial polymerization. It can be widely used in the fields of drinking water purification and sewage treatment, and has broad prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is a surface electron microscope photograph of the polyacrylonitrile ultrafiltration membrane used in Example 1;
[0033] Figure 2 This is a surface electron microscope photograph of the high-flux nanofiltration membrane with a gradient pore structure prepared in Example 4. DETAILED DESCRIPTION
[0034] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0035] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] The preparation method of the high-flux nanofiltration membrane with a gradient pore structure of this embodiment comprises the following steps:
[0039] 1. Infiltration of the first aqueous solution
[0040] The aqueous phase monomer 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane, the acid-binding agent sodium hydroxide and the solvent ultrapure water are uniformly mixed to prepare a first aqueous phase solution containing the aqueous phase monomer 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane with a mass concentration of 1.0wt% and the acid-binding agent sodium hydroxide with a mass concentration of 0.5wt%.
[0041] The first aqueous phase solution was poured onto the surface of the fixed polyacrylonitrile ultrafiltration membrane. After soaking for 2 minutes, the first aqueous phase solution was poured out and the residual solution on the surface of the polyacrylonitrile ultrafiltration membrane was removed with a rubber roller.
[0042] 2. Primary interfacial polymerization reaction
[0043] The oil phase monomer trimesoyl chloride and the organic solvent n-hexane are mixed evenly to prepare a n-hexane oil phase solution containing the oil phase monomer trimesoyl chloride with a mass concentration of 0.1 wt %.
[0044] The n-hexane oil phase solution was poured onto the surface of the polyacrylonitrile ultrafiltration membrane to carry out an interfacial polymerization reaction for 2 minutes. The oil phase solution was then poured off and the membrane surface was evenly purged with an air knife until no residual solvent was left to obtain a primary membrane.
[0045] 3. Secondary interfacial polymerization reaction
[0046] The aqueous phase monomer m-phenylenediamine and the solvent ultrapure water are mixed evenly to prepare a second aqueous phase solution containing the aqueous phase monomer m-phenylenediamine with a mass concentration of 1.0 wt %.
[0047] The second aqueous phase solution was poured onto the surface of the primary membrane to carry out a secondary interfacial polymerization reaction. The reaction time was 2 min, and then the second aqueous phase solution was poured off to obtain a composite membrane.
[0048] 4. Heat treatment
[0049] The composite membrane was placed in an oven at 85° C. for heat treatment and taken out after being kept warm for 5 minutes, thereby obtaining a high-flux nanofiltration membrane with a gradient pore structure.
[0050] The test shows that the pure water flux of this high-flux nanofiltration membrane with gradient pore structure is 25.1 L·m -2 ·h -1 bar -1 (The test temperature is 25°C and the test pressure is 0.5MPa). The interception rate for the inorganic salt sodium sulfate (concentration is 2000ppm) is 85.9%, and the interception rate for the organic pollutant ciprofloxacin (concentration is 10ppm) is 91.2%.
[0051] Example 2
[0052] The preparation method of the high-flux nanofiltration membrane with a gradient pore structure of this embodiment comprises the following steps:
[0053] 1. Infiltration of the first aqueous solution
[0054] The aqueous phase monomer bisphenol fluorene, the acid-binding agent sodium hydroxide and the solvent ultrapure water are uniformly mixed to prepare a first aqueous phase solution containing the aqueous phase monomer bisphenol fluorene with a mass concentration of 1.5 wt % and the acid-binding agent sodium hydroxide with a mass concentration of 0.5 wt %.
[0055] The first aqueous phase solution was poured onto the surface of the fixed polysulfone ultrafiltration membrane. After soaking for 2 minutes, the first aqueous phase solution was poured out and the residual solution on the surface of the polysulfone ultrafiltration membrane was removed with a rubber roller.
[0056] 2. Primary interfacial polymerization reaction
[0057] The oil phase monomer terephthaloyl chloride and the organic solvent n-hexane are mixed evenly to prepare a n-hexane oil phase solution containing the oil phase monomer terephthaloyl chloride with a mass concentration of 0.1 wt %.
[0058] The n-hexane oil phase solution was poured onto the surface of the polysulfone ultrafiltration membrane to carry out an interfacial polymerization reaction for 2 minutes. The oil phase solution was then poured off and the membrane surface was evenly purged with an air knife until no residual solvent was left to obtain a primary membrane.
[0059] 3. Secondary interfacial polymerization reaction
[0060] The aqueous phase monomer ethylenediamine and the solvent ultrapure water are mixed evenly to prepare a second aqueous phase solution containing the aqueous phase monomer ethylenediamine with a mass concentration of 1.5 wt %.
[0061] The second aqueous phase solution was poured onto the surface of the primary membrane to carry out a secondary interfacial polymerization reaction. The reaction time was 2 min, and then the second aqueous phase solution was poured off to obtain a composite membrane.
[0062] 4. Heat treatment
[0063] The composite membrane was placed in an oven at 75° C. for heat treatment and taken out after being kept warm for 5 minutes, thereby obtaining a high-flux nanofiltration membrane with a gradient pore structure.
[0064] The test shows that the pure water flux of this high-flux nanofiltration membrane with gradient pore structure is 21.2 L·m -2 ·h -1 bar -1 (The test temperature is 25°C and the test pressure is 0.5MPa). The interception rate for the inorganic salt sodium sulfate (concentration is 2000ppm) is 88.5%, and the interception rate for the organic pollutant ciprofloxacin (concentration is 10ppm) is 93.2%.
[0065] Example 3
[0066] The preparation method of the high-flux nanofiltration membrane with a gradient pore structure of this embodiment comprises the following steps:
[0067] 1. Infiltration of the first aqueous solution
[0068] The aqueous phase monomer 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane, the acid-binding agent sodium carbonate and the solvent ultrapure water are uniformly mixed to prepare a first aqueous phase solution containing the aqueous phase monomer 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane with a mass concentration of 2.0wt% and the acid-binding agent sodium carbonate with a mass concentration of 2.0wt%.
[0069] The first aqueous phase solution was poured onto the surface of the fixed polysulfone ultrafiltration membrane. After soaking for 4 minutes, the first aqueous phase solution was poured out and the residual solution on the surface of the polysulfone ultrafiltration membrane was removed with a rubber roller.
[0070] 2. Primary interfacial polymerization reaction
[0071] The oil phase monomer trimesoyl chloride and the organic solvent Isopar G are uniformly mixed to prepare an Isopar G oil phase solution containing the oil phase monomer trimesoyl chloride with a mass concentration of 0.2 wt %.
[0072] The Isopar G oil phase solution was poured onto the surface of the polysulfone ultrafiltration membrane to carry out an interfacial polymerization reaction for 4 minutes. The oil phase solution was then poured off and the membrane surface was evenly purged with an air knife until no residual solvent was left to obtain a primary membrane.
[0073] 3. Secondary interfacial polymerization reaction
[0074] The aqueous phase monomer diethylenetriamine and the solvent ultrapure water are mixed evenly to prepare a second aqueous phase solution containing the aqueous phase monomer diethylenetriamine with a mass concentration of 1.0 wt%.
[0075] The second aqueous phase solution was poured onto the surface of the primary membrane to carry out a secondary interfacial polymerization reaction. The reaction time was 4 min, and then the second aqueous phase solution was poured off to obtain a composite membrane.
[0076] 4. Heat treatment
[0077] The composite membrane was placed in an oven at 80° C. for heat treatment and taken out after being kept warm for 5 minutes, thereby obtaining a high-flux nanofiltration membrane with a gradient pore structure.
[0078] The test shows that the pure water flux of this high-flux nanofiltration membrane with gradient pore structure is 18.5 L·m -2 ·h -1 bar -1(The test temperature is 25°C and the test pressure is 0.5MPa). The interception rate for the inorganic salt sodium sulfate (concentration is 2000ppm) is 93.7%, and the interception rate for the organic pollutant ciprofloxacin (concentration is 10ppm) is 95.6%.
[0079] Example 4
[0080] The preparation method of the high-flux nanofiltration membrane with a gradient pore structure of this embodiment comprises the following steps:
[0081] 1. Infiltration of the first aqueous solution
[0082] The aqueous phase monomer bisphenol fluorene, the acid-binding agent potassium hydroxide and the solvent ultrapure water are uniformly mixed to prepare a first aqueous phase solution containing the aqueous phase monomer bisphenol fluorene with a mass concentration of 1.0 wt % and the acid-binding agent potassium hydroxide with a mass concentration of 0.5 wt %.
[0083] The first aqueous phase solution was poured onto the surface of the fixed polyacrylonitrile ultrafiltration membrane. After soaking for 2 minutes, the first aqueous phase solution was poured out and the residual solution on the surface of the polyacrylonitrile ultrafiltration membrane was removed with a rubber roller.
[0084] 2. Primary interfacial polymerization reaction
[0085] The oil phase monomer isophthaloyl chloride and the organic solvent n-hexane are mixed evenly to prepare a n-hexane oil phase solution containing the oil phase monomer isophthaloyl chloride with a mass concentration of 0.1 wt %.
[0086] The n-hexane oil phase solution was poured onto the surface of the polyacrylonitrile ultrafiltration membrane to carry out an interfacial polymerization reaction for 2 minutes. The oil phase solution was then poured off and the membrane surface was evenly purged with an air knife until no residual solvent was left to obtain a primary membrane.
[0087] 3. Secondary interfacial polymerization reaction
[0088] The water phase monomer piperazine and the solvent ultrapure water are mixed evenly to prepare a second water phase solution containing the water phase monomer piperazine with a mass concentration of 1.5 wt %.
[0089] The second aqueous phase solution was poured onto the surface of the primary membrane to carry out a secondary interfacial polymerization reaction. The reaction time was 2 min, and then the second aqueous phase solution was poured off to obtain a composite membrane.
[0090] 4. Heat treatment
[0091] The composite membrane was placed in an oven at 85° C. for heat treatment and taken out after being kept warm for 8 minutes to obtain a high-flux nanofiltration membrane with a gradient pore structure.
[0092] The test shows that the pure water flux of this high-flux nanofiltration membrane with gradient pore structure is 22.1 L·m -2 ·h-1 bar -1 (The test temperature is 25°C and the test pressure is 0.5MPa). The interception rate for the inorganic salt sodium sulfate (concentration is 2000ppm) is 88.9%, and the interception rate for the organic pollutant ciprofloxacin (concentration is 10ppm) is 94.1%.
[0093] Example 5
[0094] The preparation method of the high-flux nanofiltration membrane with a gradient pore structure of this embodiment comprises the following steps:
[0095] 1. Infiltration of the first aqueous solution
[0096] The aqueous phase monomer 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, the acid-binding agent potassium hydroxide and the solvent ultrapure water are uniformly mixed to prepare a first aqueous phase solution containing the aqueous phase monomer 9,9-bis(4-hydroxy-3-methylphenyl)fluorene with a mass concentration of 1.5wt% and the acid-binding agent potassium hydroxide with a mass concentration of 0.5wt%.
[0097] The first aqueous phase solution was poured onto the surface of the fixed polyacrylonitrile ultrafiltration membrane. After soaking for 5 minutes, the first aqueous phase solution was poured out and the residual solution on the surface of the polyacrylonitrile ultrafiltration membrane was removed with a rubber roller.
[0098] 2. Primary interfacial polymerization reaction
[0099] The oil phase monomer trimesoyl chloride and the organic solvent Isopar G are uniformly mixed to prepare an Isopar G oil phase solution containing the oil phase monomer trimesoyl chloride with a mass concentration of 0.1 wt %.
[0100] The Isopar G oil phase solution was poured onto the surface of the polyacrylonitrile ultrafiltration membrane to carry out an interfacial polymerization reaction for 5 minutes. The oil phase solution was then poured off and the membrane surface was evenly purged with an air knife until no residual solvent was left to obtain a primary membrane.
[0101] 3. Secondary interfacial polymerization reaction
[0102] The water phase monomer piperazine and the solvent ultrapure water are mixed evenly to prepare a second water phase solution containing the water phase monomer piperazine with a mass concentration of 1.0 wt %.
[0103] The second aqueous phase solution was poured onto the surface of the primary membrane to carry out a secondary interfacial polymerization reaction. The reaction time was 5 min, and then the second aqueous phase solution was poured off to obtain a composite membrane.
[0104] 4. Heat treatment
[0105] The composite membrane was placed in an oven at 90° C. for heat treatment and taken out after being kept warm for 5 minutes, thereby obtaining a high-flux nanofiltration membrane with a gradient pore structure.
[0106] The test shows that the pure water flux of this high-flux nanofiltration membrane with gradient pore structure is 16.7 L·m -2 ·h -1 bar -1 (The test temperature is 25°C and the test pressure is 0.5MPa). The interception rate for the inorganic salt sodium sulfate (concentration is 2000ppm) is 95.2%, and the interception rate for the organic pollutant ciprofloxacin (concentration is 10ppm) is 98.1%.
[0107] Example 6
[0108] The preparation method of the high-flux nanofiltration membrane with a gradient pore structure of this embodiment comprises the following steps:
[0109] 1. Infiltration of the first aqueous solution
[0110] The aqueous phase monomer 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane, the acid-binding agent sodium hydroxide and the solvent ultrapure water are uniformly mixed to prepare a first aqueous phase solution containing the aqueous phase monomer 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane with a mass concentration of 2.0wt% and the acid-binding agent sodium hydroxide with a mass concentration of 1wt%.
[0111] The first aqueous phase solution was poured onto the surface of the fixed polyacrylonitrile ultrafiltration membrane. After soaking for 5 minutes, the first aqueous phase solution was poured out and the residual solution on the surface of the polyacrylonitrile ultrafiltration membrane was removed with a rubber roller.
[0112] 2. Primary interfacial polymerization reaction
[0113] The oil phase monomer trimesoyl chloride and the organic solvent n-hexane are mixed evenly to prepare a n-hexane oil phase solution containing the oil phase monomer trimesoyl chloride with a mass concentration of 0.2 wt %.
[0114] The n-hexane oil phase solution was poured onto the surface of the polyacrylonitrile ultrafiltration membrane to carry out an interfacial polymerization reaction for 5 minutes. After that, the oil phase solution was poured off and an air knife was used to evenly blow the membrane surface until no residual solvent was left to obtain a primary membrane.
[0115] 3. Secondary interfacial polymerization reaction
[0116] The water phase monomer piperazine and the solvent ultrapure water are mixed evenly to prepare a second water phase solution containing the water phase monomer piperazine with a mass concentration of 1.0 wt %.
[0117] The second aqueous phase solution was poured onto the surface of the primary membrane to carry out a secondary interfacial polymerization reaction. The reaction time was 5 min, and then the second aqueous phase solution was poured off to obtain a composite membrane.
[0118] 4. Heat treatment
[0119] The composite membrane was placed in an oven at 95° C. for heat treatment and taken out after being kept warm for 5 minutes, thereby obtaining a high-flux nanofiltration membrane with a gradient pore structure.
[0120] The test shows that the pure water flux of this high-flux nanofiltration membrane with gradient pore structure is 15.6 L·m -2 ·h -1 bar -1 (The test temperature is 25°C and the test pressure is 0.5MPa). The interception rate for the inorganic salt sodium sulfate (concentration is 2000ppm) is 99.4%, and the interception rate for the organic pollutant ciprofloxacin (concentration is 10ppm) is 99.8%.
[0121] Example 7
[0122] The preparation method of the high-flux nanofiltration membrane with a gradient pore structure of this embodiment comprises the following steps:
[0123] 1. Infiltration of the first aqueous solution
[0124] The aqueous phase monomer 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane, the acid-binding agent trisodium phosphate dodecahydrate and the solvent ultrapure water are uniformly mixed to prepare a first aqueous phase solution containing the aqueous phase monomer 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane with a mass concentration of 1.0wt% and the acid-binding agent trisodium phosphate dodecahydrate with a mass concentration of 1wt%.
[0125] The first aqueous phase solution was poured onto the surface of the fixed polyacrylonitrile ultrafiltration membrane. After soaking for 3 minutes, the first aqueous phase solution was poured out and the residual solution on the surface of the polyacrylonitrile ultrafiltration membrane was removed with a rubber roller.
[0126] 2. Primary interfacial polymerization reaction
[0127] The oil phase monomer trimesoyl chloride and the organic solvent n-hexane are mixed evenly to prepare a n-hexane oil phase solution containing the oil phase monomer trimesoyl chloride with a mass concentration of 0.5 wt %.
[0128] The n-hexane oil phase solution was poured onto the surface of the polyacrylonitrile ultrafiltration membrane to carry out an interfacial polymerization reaction for 3 minutes. The oil phase solution was then poured off and the membrane surface was evenly purged with an air knife until no residual solvent was left to obtain a primary membrane.
[0129] 3. Secondary interfacial polymerization reaction
[0130] The aqueous phase monomer m-phenylenediamine and the solvent ultrapure water are mixed evenly to prepare a second aqueous phase solution containing the aqueous phase monomer m-phenylenediamine with a mass concentration of 1.5 wt %.
[0131] The second aqueous phase solution was poured onto the surface of the primary membrane to carry out a secondary interfacial polymerization reaction. The reaction time was 3 min, and then the second aqueous phase solution was poured off to obtain a composite membrane.
[0132] 4. Heat treatment
[0133] The composite membrane was placed in an oven at 75° C. for heat treatment and taken out after being kept warm for 3 minutes to obtain a high-flux nanofiltration membrane with a gradient pore structure.
[0134] The test shows that the pure water flux of this high-flux nanofiltration membrane with gradient pore structure is 17.6 L·m -2 ·h -1 bar -1 (The test temperature is 25°C and the test pressure is 0.5MPa). The interception rate for the inorganic salt sodium sulfate (concentration is 2000ppm) is 92.4%, and the interception rate for the organic pollutant ciprofloxacin (concentration is 10ppm) is 94.7%.
[0135] Example 8
[0136] The preparation method of the high-flux nanofiltration membrane with a gradient pore structure of this embodiment comprises the following steps:
[0137] 1. Infiltration of the first aqueous solution
[0138] The aqueous phase monomer 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane, the acid-binding agent triethylamine and the solvent ultrapure water are uniformly mixed to prepare a first aqueous phase solution containing the aqueous phase monomer 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane with a mass concentration of 1.0wt% and the acid-binding agent triethylamine with a mass concentration of 1wt%.
[0139] The first aqueous phase solution was poured onto the surface of the fixed polyethersulfone ultrafiltration membrane. After soaking for 5 minutes, the first aqueous phase solution was poured out and the residual solution on the surface of the polyethersulfone ultrafiltration membrane was removed with a rubber roller.
[0140] 2. Primary interfacial polymerization reaction
[0141] The oil phase monomer terephthaloyl chloride and the organic solvent Isopar G are uniformly mixed to prepare an Isopar G oil phase solution containing terephthaloyl chloride of the oil phase monomer with a mass concentration of 0.5 wt %.
[0142] The above Isopar G oil phase solution was poured onto the surface of the polyethersulfone ultrafiltration membrane to carry out an interfacial polymerization reaction for 5 minutes. The oil phase solution was then poured off and the membrane surface was evenly purged with an air knife until no residual solvent was left to obtain a primary membrane.
[0143] 3. Secondary interfacial polymerization reaction
[0144] The aqueous phase monomer ethylenediamine and the solvent ultrapure water are mixed evenly to prepare a second aqueous phase solution containing the aqueous phase monomer ethylenediamine with a mass concentration of 1.0 wt %.
[0145] The second aqueous phase solution was poured onto the surface of the primary membrane to carry out a secondary interfacial polymerization reaction. The reaction time was 5 min, and then the second aqueous phase solution was poured off to obtain a composite membrane.
[0146] 4. Heat treatment
[0147] The composite membrane was placed in an oven at 65° C. for heat treatment and taken out after being kept warm for 5 minutes, thereby obtaining a high-flux nanofiltration membrane with a gradient pore structure.
[0148] The test shows that the pure water flux of this high-flux nanofiltration membrane with gradient pore structure is 18.2 L·m -2 ·h -1 bar -1 (The test temperature is 25°C and the test pressure is 0.5MPa). The interception rate for the inorganic salt sodium sulfate (concentration is 2000ppm) is 91.5%, and the interception rate for the organic pollutant ciprofloxacin (concentration is 10ppm) is 93.8%.
[0149] Comparative Example 1
[0150] Except that ultrapure water is used to replace the second aqueous phase solution of Example 6 in step 3, the rest is the same as Example 6.
[0151] The test shows that the pure water flux of this high-flux nanofiltration membrane with gradient pore structure is 36.7 L·m -2 ·h -1 bar -1 (The test temperature is 25°C and the test pressure is 0.5MPa). The interception rate for the inorganic salt sodium sulfate (concentration is 2000ppm) is 75.5%, and the interception rate for the organic pollutant ciprofloxacin (concentration is 10ppm) is 80.2%.
[0152] Comparative Example 2
[0153] The process is the same as that of Example 6 except that in step 1, the aqueous phase monomer piperazine is used to replace 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane.
[0154] The test shows that the pure water flux of this high-flux nanofiltration membrane with gradient pore structure is 5.6 L·m -2 ·h -1 bar -1 (The test temperature is 25°C and the test pressure is 0.5MPa). The interception rate for the inorganic salt sodium sulfate (concentration is 2000ppm) is 99.6%, and the interception rate for the organic pollutant ciprofloxacin (concentration is 10ppm) is 99.8%.
[0155] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high-flux nanofiltration membrane with a gradient pore structure, characterized in that: The steps include the following steps in order: S1: pouring the first aqueous phase solution onto the surface of the fixed porous support membrane, and after soaking for a certain period of time, pouring out the first aqueous phase solution and removing the residual solution on the surface of the porous support membrane; S2: pouring the oil phase solution onto the surface of the porous support membrane to carry out an interfacial polymerization reaction, then pouring out the oil phase solution and blowing the surface of the porous support membrane until there is no residual solvent, thereby obtaining a primary membrane; S3: pouring the second aqueous phase solution onto the surface of the primary membrane to carry out a secondary interfacial polymerization reaction, and then pouring out the second aqueous phase solution to obtain a composite membrane; S4: heat-treating the composite membrane to obtain a high-flux nanofiltration membrane with a gradient pore structure.
2. The preparation method according to claim 1, characterized in that: The porous support membrane is selected from any one of cellulose acetate ultrafiltration membrane, polyethylene ultrafiltration membrane, polysulfone ultrafiltration membrane, polyethersulfone ultrafiltration membrane, polyamide ultrafiltration membrane and polyacrylonitrile ultrafiltration membrane.
3. The preparation method according to claim 1, characterized in that: The solute of the first aqueous phase solution includes an aqueous phase monomer and an acid binding agent; the mass concentration of the aqueous phase monomer in the first aqueous phase solution is 1-10wt%, and the mass concentration of the acid binding agent in the first aqueous phase solution is 0.1-5wt%; Preferably, the aqueous phase monomer is selected from at least one of self-microporous polymers containing at least two hydroxyl groups; Preferably, the aqueous phase monomer is selected from at least one of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane, 3,3,3',3'-tetramethyl-1,1'-spiro BI (indane)-6,6'-diol, 9,9-bis (4-hydroxy-3-methylphenyl) fluorene and bisphenol fluorene; Preferably, the acid binding agent is selected from at least one of triethylamine, sodium hydroxide, potassium hydroxide, pyridine, N,N-diisopropylethylamine, trisodium phosphate dodecahydrate and sodium carbonate.
4. The preparation method according to claim 1, characterized in that: In step S1, the first aqueous phase solution is infiltrated on the surface of the porous support membrane for 1-10 minutes.
5. The preparation method according to claim 1, characterized in that: The solute of the oil phase solution includes an oil phase monomer, and the oil phase monomer is selected from at least one of polyacid chlorides; Preferably, the oil phase monomer is selected from at least one of trimesoyl chloride, terephthaloyl chloride and isophthaloyl chloride; Preferably, the mass concentration of the oil phase monomer in the oil phase solution is 0.1-5wt%; Preferably, the solvent of the oil phase solution is selected from at least one of n-hexane, Isopar G and toluene.
6. The preparation method according to claim 1, characterized in that: The solute of the second aqueous phase solution contains only aqueous phase monomers, and the aqueous phase monomers are selected from at least one of amine compounds; Preferably, the aqueous phase monomer is selected from at least one of m-phenylenediamine, piperazine, ethylenediamine and diethylenetriamine; Preferably, the mass concentration of the aqueous phase monomer in the second aqueous phase solution is 1-10 wt %.
7. The preparation method according to claim 1, characterized in that: The first interfacial polymerization reaction time is 1-10 min; the second interfacial polymerization reaction time is 1-10 min.
8. The preparation method according to claim 1, characterized in that: The heat treatment temperature is 50-100°C, and the heat treatment time is 1-15min.
9. A high flux nanofiltration membrane with a gradient pore structure, characterized in that: Prepared according to any one of the preparation methods of claims 1-8.
10. Use of the high-flux nanofiltration membrane according to claim 9 in water treatment.
Citation Information
Cited By
High-rejection-rate reverse osmosis membrane for seawater desalination as well as preparation method and application of high-rejection-rate reverse osmosis membrane
CN120571431A
Green preparation process of composite film
CN120586651A